A study and investigation of Small Antenna Efficiency Measurement using Reverberation Chamber - Azremi, Abdullah Al Hadi; Jack, Soh Ping; Anuar, Mat Safar (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my